PSYCHOLOGICAL COMMUNICATION IN DIGITAL PHOTOGRAPHY - Tan, Ellyana Mohd Muslim; Lazim, Nur Aniza Mohd; Mat Hussin, Mohd Shahrizal; Ishak, Siti Norfatulhana (specta, 2024)
The study examines the impact of digital transformation on photograph visuals using Photo Elicitation Interview (PEI) as a method of persuasion for participant. 30 participants were participated in the study, they were given random 100 digital images, in online platform. Participants selected one images and answer one simple questions of how the pictures reflect them. The objective of the study to seek visual analogies are beneficial not only on the visual surface, but also in indicating the deeper meaning behind the image. The study discusses a vital indicator in comprehending photography mentally. Persuade the audience to grasp the image and explain it by using Connotative indirect message and Denotative, which frequently offers direct communication. Certainly, the faculty of picture reaction to auto recognition machine learning is parallel to image analysis on who and where the image was taken as a guidance to recollections, while the system will set it to remind and recall the memory. The data analysis from the study recommends additional investigation and provides the present spectrum of visual investigations. Additionally, it is encouraged to participate as a data provider to provide details on national proposals, alternative solutions, and improved knowledge to support the United Nations 2030 Agendas, namely the Sustainable Development Goals.